Quality of life assessment of children with thalassemia - Masyitah Sri Wahyuni; Muhammad Ali; Nelly Rosdiana; Bidasari Lubis (Paediatrica Indonesiana, 2011)
Background Thalassemia is a chronic disease that is becoming aÂ major health problem in the world, including the Mediterranean,Â as well as Malaysia, Thailand and Indonesia. This condition clearlyÂ affects the patient's quality of life, because of the condition itself andthe effects of treatment. Assessment is needed to detennine actionsÂ to be taken to improve the quality of life in thalassemic children.Objective To assess the differences in quality of life of thalassemicÂ children compared to their normal siblings.Methods We perfonned a crossô€Œsectional study from May 2010Â until June 2010 in H. Adam Malik Hospital, Medan and the homeÂ of a member of the North Sumatra Chapter of the Association ofÂ Parents of Thalassemia Sufferers (perhimpunan Orangtua PenderitaTalasemia Indonesia, POPTI). Thalassemic children aged 5-18Â years and their age and genderô€Œadjusted siblings were divided intoÂ two groups: case group and control group. Parents and childrenÂ were asked to fill the PedsQL (Pediatric Quality of life Inventory)version 4.0 questionnaire to assess their quality of life.Results There were 59 children in each group. The assessments ofÂ four quality of life domains in the thalassemic group vs the controlÂ group showed the folloMng: physical function 53.1 vs 71.5 (95%Â CI -21.41 to -15.26, Pô€O.OOOI), emotional function 50.9 vs 62.9Â (95% CI -16.82 to -7 .41, Pô€O.OOO 1), social function 62.5 vs 72.8Â (95% CI-13.50 to -7.01, Pô€O.OOOI) and school function 36.2 vsÂ 56.0 (95% CI -22.95 to -16.71, Pô€O.OOOI). Total scores were 50.9Â vs 66.1 (95% CI -18.20to -13.12, Pô€O.OOOI). School function wasÂ the most affected parameter studied, with thalassemic childrenÂ scoring lower than the control group.Conclusion There were significant decreases in the quality ofÂ life parameters in the thalassemic group compared to the controlÂ group. Thalassemic children have poorer quality oflife comparedÂ to their nonnal siblings, Mth school function being the mostaffected domain.Â